Aircraft head-up display surface guidance system - Gu, Jinxin (Cranfield University, 2013)
The continues growth in aviation and passenger numbers is putting more pressure on airports to become more efficient in order to reduce the number of delays due to external factors such as weather, pilot deviation/errors and airport maintenance traffic. As major hubs (e.g. Heathrow, New York or Paris) expand in size to accommodate more traffic; aircraft surface movement and management become more complex and the margin for error is even lower. The traditional airport traffic management tools in large airports are increasingly stretched to the limit in meeting safety and traffic throughput requirements. This presents a huge challenge to the efficiency of airport operations because of the increased number of departures and arrivals at those airports. New technology for surface movement needs to be implemented in order to increase the safety and airport capacity. The federal aviation authorities in the USA was first to introduce the concept of Advanced Surface Movement Guidance and Control System (A-SMGCS) to address this problem in commercial airdrome operations. The system facilitates pilot recognition of the route designated by the traffic controllers and uses warning information to make them aware of any potential deviations/incursions. The system is introduced to enhance the efficiency of surface movement by increasing the aircraft taxiing speed and reducing any pilot errors during bad weather conditions. This thesis focuses on the surface guidance system for aircraft equipped with head-up display. A simulation model of the virtual environment using FlightGear and Simulink is developed based on the study of a moving map and surface guidance system for Head-Up Display (HUD) to assign the route, guide the aircraft on the designated taxiway and avoid potential conflict with other aircraft. A method of generating an airport in FlightGear and driving an airport moving map to rotate and move is also illustrated which includes the data processing flow chart and system flow chart. The Ordnance Survey National Grid and world coordinate system is discussed and used to transform from GPS latitude and longitude data to the position on Nation Grid. There is also an explanation of the 3D viewing process to generate the virtual taxiway geometries on the HUD. The communication between the traffic console and airplane is also discussed.
Keywords: Airport; guidance; runway incursion; routing; surface movement; taxiway